1996
DOI: 10.1021/ma9503423
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Free Volume Change on the Relative Permittivity and Refractive Index in Fluoropolyimides

Abstract: The often observed decrease in relative permittivity ( ′) and refractive index (n) that accompanies fluorine substitution is the result of several effects. Fluorine replacement for hydrogen is known to decrease local electronic polarization and is thought to frequently increase fractional free volume. Both of these effects can independently decrease ′ and n, and this paper attempts to assign the observed decreases between these mechanisms for a series of hydrogen/fluorine polyimide analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 212 publications
(187 citation statements)
references
References 10 publications
4
181
2
Order By: Relevance
“…A correlation of high free volume and low dielectric constant has been previously reported for polyimides [8][9][10]. In these investigations positron lifetime spectroscopy and group additivity methods were used to quantify free volume fractions.…”
Section: Free Volumementioning
confidence: 90%
“…A correlation of high free volume and low dielectric constant has been previously reported for polyimides [8][9][10]. In these investigations positron lifetime spectroscopy and group additivity methods were used to quantify free volume fractions.…”
Section: Free Volumementioning
confidence: 90%
“…Different weights of PTS were added to each portion to get PAA± PTS solutions with different weight ratios of PTS to APTS± PAA (8,16,24,36,50,70, 100, 140 w/w%). Stirring was continued at room temperature for 15 h, to give a homogenous solution.…”
Section: Preparation Of Paa±pts Solution and Pi/pssq-like Hybrid ®Lmsmentioning
confidence: 99%
“…Thus, according to literature data [42,43], a higher free volume determines a lower dielectric constant. In Figure 3 it can be observed that dielectric constants of Epiclon-derived PIs containing ether bridges are around 2.8 at 1 MHz, recommending this type of PIs as interlevel dielectric layers in the fabrication of semiconductor chips and multichip packaging structures [44].…”
Section: Refractive Index Optical Gap and Absorption Edgesmentioning
confidence: 77%